Rapid induction of antigen-specific CD4+ T cells is associated with coordinated humoral and cellular immunity to SARS-CoV-2 mRNA vaccination - Painter, Mark M.; Mathew, Divij; Goel, Rishi R.; Apostolidis, Sokratis A.; Pattekar, Ajinkya; Kuthuru, Oliva; Baxter, Amy E.; Herati, Ramin S.; Oldridge, Derek A.; Gouma, Sigrid; Hicks, Philip; Dysinger, Sarah; et al. (Immunity (Cambridge, Mass.), 2021)
SARS-CoV-2 mRNA vaccines have shown remarkable clinical efficacy, but questions remain about the nature and kinetics of T cell priming. We performed longitudinal antigen-specific T cell analyses on healthy SARS-CoV-2-naive and recovered individuals prior to and following mRNA prime and boost vaccination. Vaccination induced rapid antigen-specific CD4+ T cell responses in naive subjects after the first dose, whereas CD8+ T cell responses developed gradually and were variable in magnitude. Vaccine-induced Th1 and Tfh cell responses following the first dose correlated with post-boost CD8+ T cells and neutralizing antibodies, respectively. Integrated analysis revealed coordinated immune responses with distinct trajectories in SARS-CoV-2-naive and recovered individuals. Last, whereas booster vaccination improved T cell responses in SARS-CoV-2-naive subjects, the second dose had little effect in SARS-CoV-2-recovered individuals. These findings highlight the role of rapidly primed CD4+ T cells in coordinating responses to the second vaccine dose in SARS-CoV-2-naive individuals. [Display omitted] •mRNA vaccines generate antigen-specific T cells in a coordinated immune response•Vaccine-induced T cells resemble the durable memory cells primed by infection•Th1 and cTfh cell responses to the first dose correlate with second-dose responses•SARS-CoV-2-recovered individuals benefit from the first but not the second dose SARS-CoV-2 mRNA vaccines have demonstrated remarkable efficacy, but T cell responses to vaccination have not been well studied. In a longitudinal cohort, Painter et al. show that mRNA vaccines activate SARS-CoV-2-specific T cells that could contribute to durable immunity. The findings highlight the central role of T cells in the two-dose vaccine regimen for individuals not previously infected with SARS-CoV-2.